Theoretical Investigation of IR and Geometry of the S-benzyl-β-N-(2-furylmethylketone)dithiocarbazate Schiff Base by Semi-Empirical Methods - KUMAR, D.; AGRAWAL, M.C.; TOMAR, RADHA; SINGH, KAMAN; ARORA, KISHORE; SINGH, RAJEEV; BHARDWAJ, M.K.; SINGH, BHOOP; BARHADIYA, H.S.; TAIGER, R.K.; GUPTA, ANJANA (Asian Journal of Chemistry, 2010)
Schiff bases of alkyl/aryl dithiocarbazate and their transition metal complexes have received much attention due to their biological activities. Performance of Semi-empirical AM1, PM3, MNDO, MNDO-d methods have been tested to find the best auxiliary tool for the IR frequencies, geometry and electron densities. For bond lengths, the correlation coefficient obtained for AM1, PM3, MNDO and MNDO-d methods are 0.96, 0.990, 0.983 and 0.976, respectively. Out of the four semi-empirical methods PM3 produces most satisfactory correlation (cc = 0.990) between experimental and calculated bond length. In the case of bond angles, correlation coefficients are 0.836, 0.742, 0.706 and 0.685 for AM1, PM3, MNDO and MNDO-d methods, respectively. Thus AM1 method gives most satisfactory correlation (cc = 0.836). Out of two nitrogen atoms azo-methine nitrogen carried more electron density. For fundamental vibrational frequencies, the correlation coefficient obtained for AM1, PM3, MNDO and MNDO-d methods are 0.926, 0.967, 0.760, and 0.969, respectively. Out of the four semiempirical methods MNDO-d yields most satisfactory correlation (cc = 0.969) between experimental and calculated fundamental vibrational frequencies.